2014
DOI: 10.1590/1981-5344/1818
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores para o novo serviço público: uma análise bibliométrica e sistêmica

Abstract: Este artigo objetiva investigar a ocorrência de trabalhos que exploram indicadores para o novo serviço público, por meio de uma análise bibliométrica e sistêmica. Utilizaramse cinco bases de dados de forma a localizar estudos sobre o tema no período de 1992 a 2012. Pôde-se constatar a carência e a insipiência de publicações sobre o tema em questão, o que sugere a oportunidade e um relativo espaço para pesquisas futuras. Palavras-chave:Análise Bibliométrica; Análise Sistêmica; Indicadores; Novo Serviço Público;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
4
0
4
Order By: Relevance
“…The relationship between the articles in Figure 2 revealed numbers (4) 18 and (7) 21 to be considered "authority articles" or "base articles" which are the main references for other authors and the subject of the greatest number of citations 14,30 In addition to the authority articles, there are also "hub" or "connection" articles 14 ,which condense important information from previous works, connecting them with more recent studies, and which are frequently cited, identified by numbers(8) 22 , (10) 24 , (13) 27 and (15) 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the articles in Figure 2 revealed numbers (4) 18 and (7) 21 to be considered "authority articles" or "base articles" which are the main references for other authors and the subject of the greatest number of citations 14,30 In addition to the authority articles, there are also "hub" or "connection" articles 14 ,which condense important information from previous works, connecting them with more recent studies, and which are frequently cited, identified by numbers(8) 22 , (10) 24 , (13) 27 and (15) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The steps for the analysis performed here follow three procedures: the definition of the database to be consulted and the criteria to be used for collection; the collection of data; and the representation and analysis of the same 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Exploratory and descriptive study of the bibliometric type conducted through the following steps: defining the database and the criteria to be used for the collection, collection of data and the representation and analysis of these SELIG, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Representação e análise desses dados. 7 Koskinen et al alertam sobre a seleção da base de dados a ser utilizada, pois deve haver compatibilidade dessa escolha com os objetivos da pesquisa e o alcance dos resultados. 8 Assim, para este estudo foi selecionada a base ISI Web of Knowledge/Web of Science (WoS) por ela ser reconhecida academicamente como uma das mais importantes bases de periódicos, além de ser relevante e pioneira na reunião de periódicos de mais de cem áreas do conhecimento, incluída a da Saúde.…”
Section: Métodosunclassified